Bye bye planet Pluto - Cook, Nicola (United States : BBC Active, 2006)
Looks at the scientific debate that resulted in Pluto's demotion to a minor planet
Title from title screen
Originally broadcast on the television program Horizon
Editor, Andrew Cohen ; graphic, Jason White, Stephen Matthes ; sound, Marc Stewardt...[et al.] ; photography, Tim Cragg, Sam Key
Narrator: Ian Holm
Keywords: Pluto (Planet)